Effect of social participation on the development of physical frailty: Do type, frequency and diversity matter?. (September 2021) - Xie, Boqin; Ma, Chenjuan
Highlights: Promoting social participation may be a way to mitigate the burden associated with physical frailty in community-dwelling older adults. The extent of the association between social participation and onset of physical frailty differs by the specific type of activities engaged in. The effect of frequency of social participation on onset of physical frailty depends on its type. More diverse social participation leads to a greater decrease in the risk of incident frailty. Abstract: Background: Little is known about the longitudinal association between social participation and incident frailty in community-dwelling older adults in general and particularly in China. This study examined the impact of type, frequency and diversity of social participation on incident physical frailty at two-year follow-up. Method: Longitudinal data from three waves of the China Health and Retirement Longitudinal Study were used. Older adults who were non-frail and aged 60 years or more at baseline and had information on physical frailty at follow-up were included. Frailty was measured using the modified frailty phenotype criteria. Social participation was measured as the type, frequency and diversity of engagement in social activities, including interacting with friends, playing group games, participating in sports clubs, community-related organizations, and voluntary activities. Results: A total of 6959 eligible respondents were included. Playing group games (OR=0.73, 95%CI=0.55–0.96) or participating in the activities of sports clubs (OR=0.54, 95%CI=0.34–0.85) once or more times per week led to a decreased risk of developing frailty in two years whereas participating in voluntary activities occasionally (OR=0.50, 95%CI=0.30–0.84) had a protective effect on the development of frailty. More diverse social participation was significantly associated with lower risk of incident frailty at two-year follow-up. Conclusions: The association between social participation and onset of physical frailty differed by the specific type and frequency of the activities that older adults engaged in. Promoting social participation of various types and at an appropriate frequency may be a promising way to mitigate the burden associated with physical frailty among older adults.